UPAYA PENINGKATKAN HASIL BELAJAR SERVIS BAWAH BOLA VOLLEY MELALUI MODEL PEMBELAJARAN RESIPROKAL BAGI PESERTA DIDIK KELAS IV SDN 2 KARANGKEMOJING - Abdul Kholik (Pusat Studi Pendidikan dan Kreativitas Guru, 2018)
Classroom action research shows the results of the study illustrates thefollowing. In the initial conditions only 9 of 21 students or 42.85% of studentswho complete learning. In the first cycle there is an increase in the ability ofenough students, as many as 7 of 21 students or 33.33% to 16 out of 21 studentsor 76.19% of students complete learning. The second cycle is the improvementof students’ ability as much as 4 from 21 students as well or 19.04%. So the totalnumber of students who complete the study to 20 of 21 students or 95.23%students complete study. Only one student is not complete learning. Thisis because students’ thinking power and physical ability of the child is low.Based on the empirical data collected in classroom action research done bythe researcher has succeeded to improve the learning result of voley ball gamematerial through the reciprocal learning model for fourth grade students of SDNegeri 2 Karangkemojing in second semester of academic year 2015/2016.